A randomized 'N-of-1' single blinded clinical trial of barbed dermal sutures vs. smooth sutures in elective plastic surgery shows differences in scar appearance two-years post-operatively. Issue 7 (July 2015) - Koide, S.; Smoll, N.R.; Liew, J.; Smith, K.; Rizzitelli, A.; Findlay, M.W.; Hunter-Smith, D.J.
Summary Background Barbed sutures have unidirectional circumferential shallow barbs, which distribute tension throughout the wound and close wound securely without the need to tie knots. Objectives We compare two different methods of wound closure in elective plastic surgical cases: barbed 3/0 V-Loc™180 suture and smooth 3/0 Maxon™ sutures, both polyglyconate monofilament synthetic absorbable sutures. We assessed the aesthetic long-term results with a minimum two year follow up. Methods This is a prospective, randomized controlled study with internal control. A single surgeon performed all cases. Patients who underwent elective operations that involved long wound closure were enrolled in the study. Each patient acted as their own internal control with half their wound being sutured with 3/0 V-Loc™180 barbed suture and the other half with smooth 3/0 Maxon™ deep dermal sutures and then a subcuticular skin closure. In both groups, the superficial fascial system was closed with 1 Vicryl interrupted sutures on both sides. Long-term cosmesis was evaluated using the modified Hollander cosmesis score by review of standardized postoperative photographs by 9 blinded plastic surgeons and specialist registrars. Results The study reports on 33 female patients. The time taken for wound closure was significantly reduced using the barbed suture (p < 0.001). There was no difference in the complication ratio in either group. Two-year aesthetic outcome was significantly superior when using the barbed suture (p = 0.0075). Conclusion Barbed sutures closure of long wounds is faster and produces a better long-term aesthetic outcome than smooth sutures.